Intention-Based Transcultural Family Empowerment Model for Complementary Feeding Practices: A Structural Equation Modeling Approach - Agusta Dian Ellina; Novian Mahayu Adiutama; Yudisa Diaz Lutfi Sandi; Wardah Fauziah; Dewi Rahayu Ningsih; Esti Andarini; Sandi Alfa Wiga Arsa; Nuridha Fauziyah (Journal of Ners and Midwifery, 2026)
Stunting remains a major public health concern in Indonesia, particularly among children aged 6–24 months. The quality of complementary feeding is strongly influenced by cultural norms and family dynamics. This study aimed to validate a previously developed transcultural care-based family empowerment model by integrating “intention” as a mediating factor in behavioral change. A cross-sectional study was conducted involving 530 families in Kediri, East Java, Indonesia. Data were collected using structured questionnaires and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings revealed that “intention” served as a robust mediator between family empowerment and complementary feeding quality (β = 0.45; p < 0.001), with an R² value of 0.69. These results underscore that nutritional behavior within families is shaped not only by knowledge and cultural values but also by psychological intention to act. The expanded model—an intention-based transcultural family empowerment framework—enhances behavioral predictability and broadens the application of transcultural care theory in community nursing contexts. Future research is recommended to apply longitudinal or intervention-based designs to examine changes in family intention over time and their impact on child nutrition outcomes. Expanding the application of this model to other health behaviors and cultural settings may further strengthen its theoretical and practical relevance in community nursing and public health contexts.